Treatment of a severe skeletal Class II malocclusion through growth modification: a problem-oriented case report - Yan Yimeng; Ouyang Zhiqiang; Tong Fei (Sciendo, 2023)
A skeletal Class II malocclusion is an anteroposterior discrepancy resulting from a combination of skeletal and dental factors. In adolescent patients, it is possible to leverage their growth potential to address bone deformities and minimise the need for future surgical interventions. In the present case report, a combination treatment approach was adopted which included a functional appliance, fixed appliances, and temporary anchorage support, to treat a 13-year-old Chinese male with a severe skeletal Class II malocclusion. After a treatment duration of 36 months, the patient achieved a favourable occlusion and an improved facial profile. Subsequently, a stable occlusal relationship and balanced facial proportions were maintained during a 2-year retention period.